2020
DOI: 10.1159/000506842
|View full text |Cite
|
Sign up to set email alerts
|

Response to Checkpoint Inhibition in Non-Small Cell Lung Cancer with Molecular Driver Alterations

Abstract: Aims: Non-small cell lung cancer (NSCLC) patients with EGFR mutations do not respond well to checkpoint inhibitors. However, little is known about the activity of immunotherapy in NSCLC with other driver mutations. The increasing use of next-generation sequencing (NGS) leads to molecular findings that face the clinician with problems while choosing the best treatment. This study aims at analyzing response of NSCLC with driver mutations to immunotherapy. Patients and Methods: We retrospectively included 84 NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…ASCO/CAP/IASLC/AMP guidelines recommend a TAT of 10 working days between sample receipt and reporting of molecular test results [28]; a recent European Expert Group suggests a general timeframe of 5 working days for molecular test results [75]. Delays in TAT can lead to less efficient use of targeted therapies; for example, initiating immunotherapy before mutation test results are received can mean EGFR tyrosine kinase inhibitors are used as second-line versus first-line agents [76,77].…”
Section: Practical Challenges (Turnaround Time Test Complexity Reflex Testing)mentioning
confidence: 99%
“…ASCO/CAP/IASLC/AMP guidelines recommend a TAT of 10 working days between sample receipt and reporting of molecular test results [28]; a recent European Expert Group suggests a general timeframe of 5 working days for molecular test results [75]. Delays in TAT can lead to less efficient use of targeted therapies; for example, initiating immunotherapy before mutation test results are received can mean EGFR tyrosine kinase inhibitors are used as second-line versus first-line agents [76,77].…”
Section: Practical Challenges (Turnaround Time Test Complexity Reflex Testing)mentioning
confidence: 99%
“…Mutant KRAS was associated with increases in tumor infiltrating lymphocytes, PD-L1 expression and tumor mutational burden [ 182 , 183 ]. However, while Gianoncelli et al observed no significant differences between KRAS + and non- KRAS NSCLC patients in terms of progression-free or overall survival [ 184 ], Kauffmann-Guerrero et al reported a positive outcome for KRAS mutations in response to immune checkpoint inhibitors [ 185 ]. Molecular diversity within KRAS + NSCLC patients offers an attractive biological explanation for such discrepancy in results [ 186 ].…”
Section: New Optimism For Targeting Kras Mutatimentioning
confidence: 99%
“…In addition, it has been shown that alterations in certain genes, such as KRAS, TP53, MET, ARID1A and others are enriched in immunotherapy responsive patients. Thus, their identi cation could lead to such treatment option (80)(81)(82).…”
Section: Immunotherapy Biomarkersmentioning
confidence: 99%